Employee Performance in Restaurants: A Conventional Approach to Archive Management and Office Space Design - Tettie Setiyarti; Ni Made Purnamasari; Ni Ketut Laswitarni; Ida Ayu Trisna Wijayanthi; Ida Bagus Swaputra (International Journal of Advanced Multidisciplinary, 2025)
This study explores the impact of archival activities and office layout on employee performance in the restaurant industry, specifically focusing on Bejana Restaurant in Nusa Dua, Bali. These two aspects are often overlooked, yet they play a critical role in ensuring proper record-keeping and an efficient workspace, both of which can positively affect employee performance. The research employs various data analysis methods, including validity and reliability tests, multiple linear regression, and tests for linearity, normality, heteroscedasticity, and multicollinearity. The findings show that while the F-test significance value was 0.031, confirming that the regression model can be used to analyze employee performance, neither archival arrangement nor office layout had a significant impact on employee performance.